LEGAL CONSEQUENCES OF SELLING ANTIBIOTICS DRUGS WITHOUT DOCTOR’S PRESCRIPTION IN PHARMACIES - Khomsiyah; Zamroni, Mohammad; Adriano (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
The use of antibiotic drugs is subject to statutory regulations, which require a doctor's prescription for purchase. Antibiotic drugs are classified as